INCLUSION OF MODERN TECHNIQUES AND SUBJECTS IN MITHILA FOLK ART - Kumari, Jyoti; tonk, Lucky (International Journal of Research -GRANTHAALAYAH, 2026)
Mithila folk art is considered a unique confluence of tradition, spirituality and nature. It is historically a traditional folk art of Mithila region of Bihar, also known as Madhubani Art. Initially this art was created on mud walls, along with the use of natural mediums like Bamboo (Brush), natural colours like Yellow (turmeric), Blue (Indigo), Red (Safflower) White (rice) etc. In which religious, cultural and symbolic themes were included. But with the change of time, new experiments can now be seen in subject, medium and techniques. Through the use of various digital tools and the influence of social media are opening new avenues for creative entrepreneurship and cultural expression in Mithila today. It serves as a bridge between traditional values and modern techniques. So that Mithila art remains relevant in the modern context while staying connected to its roots. This research paper focuses on the inclusion of modern techniques and themes in Mithila folk Art.